2000 Mandinka Epic Campus Promotion - (:unkn) unknown (My University, 2018)
Featuring focal points from the 1999-2000 season of the Artists Series.
Photo of on-campus promotion for The Mandinka Epic, presented Feb. 18, 2000.
Keywords: Performing arts